Advancement in photocatalyst and piezophotocatalyst micromotor for environmental remediation: a concise review - Rosdi, Hafawati (2024)
This review analyses recent advancements in the synthesis and environmental applications of photocatalysts and piezophotocatalysts, pivotal for organic pollutant degradation and water remediation. Traditional semiconductor photocatalysts often face rapid electron-hole recombination and limited visible light absorption. Innovations have led to the development of semiconductor heterojunctions that enhance photocatalytic efficiency by improving charge separation and expanding light absorption. This review emphasizes semiconductor-semiconductor and semiconductor-metal interfaces, which significantly improve photocatalytic performance. Additionally, piezophotocatalysts have emerged, utilizing mechanical energy to augment chemical reactions, thereby increasing efficiency and applicability under various conditions. The review also highlights the role of photocatalyst-based microrobots in targeted water treatment, utilizing local chemical energy for precise operations. These advancements showcase the potential of photocatalytic and piezophotocatalytic technologies in environmental sustainability, highlighting current trends and future prospects for effective environmental remediation.